Model Pengembangan dan Strategi Branding Buah Salak Merah - Olyvia Ririmasse; Dessy Balik (Univiversitas Dr. Djar Wattiheluw, 2023)
The absence of market and product innovation of buah salak merah are important problems faced by the farming community in Riring Village. Moreover, there has been no government attention in empowering this local product. For this reason, the research was conducted to design a development model and branding strategy of buah salak merah. Data were analyzed using a qualitative approach which consisted of three activities that occurred simultaneously, namely: reducing data, presenting data and conclusions. Data were obtained from experts, namely farmers and government. The implication of this research is to produce the elaboration model between farmers and the government to increase the innovation of development and Branding Strategy based on Local Wisdom. The result indicates Farmers need knowledge, skills, processing equipment, market and the attention of the Riring Village Government and SBB District Government to develop buah salak merah.